Inflammatory Response to Regulated Cell Death in Gout and Its Functional Implications - Zhao, Jianan; Wei, Kai; Jiang, Ping; Chang, Cen; Xu, Lingxia; Xu, Linshuai; Shi, Yiming; Guo, Shicheng; Xue, Yu; He, Dongyi (Frontiers in Immunology, 2022)
Gout is a chronic inflammatory arthritis disease characterized by hyperuricemia and is caused by interactions between genetics, epigenetics, and metabolism. Acute gout symptoms are triggered by the inflammatory response to monosodium urate crystals, which is mediated by the innate immune system and immune cells (e.g., macrophages and neutrophils), NLRP3 inflammasome activation, and pro-inflammatory cytokine (IL-1β) release. Recent studies indicated that multiple programmed cell death pathways are involved in the inflammatory response, including pyroptosis, NETosis, necroptosis, and apoptosis, to initiate inflammatory reactions. In this review, we explore the correlation and interactions among these factors and their roles in the pathogenesis of gout to provide future research directions and possibilities for identifying potential novel therapeutic targets and enhancing the understanding of the pathogenesis of gout.